Exploring Visuo-Haptic augmented reality user interfaces for Stereo-tactic neurosurgery planning - Eck, Ulrich; Stefan, Philipp; Laga, Hamid; Sandor, Christian; Fallavollita, Pascal; Navab, Nassir (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2016)
Stereo-tactic neurosurgery planning is a time-consuming and complex task that requires detailed understanding of the patient anatomy and the affected regions in the brain to precisely deliver the treatment and to avoid proximity to any known risk structures. Traditional user interfaces for neurosurgery planning use keyboard and mouse for interaction and visualize the medical data on a screen. Previous research, however, has shown that 3D user interfaces are more intuitive for navigating volumetric data and enable users to understand spatial relations more quickly. Furthermore, new imaging modalities and automated segmentation of relevant structures provide important information to medical experts. However, displaying such information requires frequent context switches or occludes otherwise important information. In collaboration with medical experts, we analyzed the planning workflow for stereo-tactic neurosurgery interventions and identified two tasks in the process that can be improved: volume exploration and trajectory refinement. In this paper, we present a novel 3D user interface for neurosurgery planning that is implemented using a head-mounted display and a haptic device. The proposed system improves volume exploration with bi-manual interaction to control oblique slicing of volumetric data and reduces visual clutter with the help of haptic guides that enable users to precisely target regions of interest and to avoid proximity to known risk structures.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Augmented reality; Haptics; Neurosurgery; Planning